Southwest Asia : the Transpacific geographies of Chicana/o literature - Sae-Saue, Jayson Gonzales (Rutgers University Press, 2016)
Southwest Asia investigates why key Chicana/o writers, from the 1950s to the present day, have persistently referenced Asian people and places in the course of articulating their political ideas. Raising concerns about how these texts invariably marginalize their Asian characters and suggesting that darker legacies of imperialism and exclusion might lurk beneath their utopian visions of a Chicana/o nation, Jayson Gonzales Sae-Saue takes our conception of Chicana/o literature as a transnational movement in a new direction.
Keywords: American literature -- Mexican American authors -- History and criticism.; Mexican Americans -- Asia.; Internationalism in literature.; Littérature américaine -- Auteurs américains d'origine mexicaine -- Histoire et critique.; Américains d'origine mexicaine -- Asie.; Internationalisme dans la littérature.; LITERARY CRITICISM -- American -- General.; LITERARY CRITICISM -- American -- Asian American.; American literature -- Mexican American authors; Internationalism in literature; Mexican Americans; Asia; Criticism, interpretation, etc.